Narratives at Play in Aeschylus : Perspectives on Genre and Poetics - Gianvittorio-Ungar, Laura, (Classical Studies E-Books Online, Collection 2024., 2025)
So little happens in the earliest surviving plays that their dramatic status almost escapes the reader. This calls for a revision of traditional views and historiographies of dramatic literature: for example, how did action come to define drama, and how did these genre developments influence reception? Above all, what constitutes drama when action is as optional as it apparently was in the 470s-460s BCE? This book rethinks Aeschylean theatre as a practice that combines elements of storytelling with enacted responses to them, and reads the literary remains of this practice from cross-generic perspectives (ancient, modern, and transhistorical). Recognizing the importance of embedded narratives in Aeschylus helps us adapt our poetological frameworks to his art at last, rather than vice versa.